Potential of chrysomya megacephala (diptera:calliphoridae) maggot meal as protein source in Tilapia (Oreochromis sp.) feed / Sing Kong Wah - Sing, Kong Wah (2012)

(untitled)
Currently, fishmeal is a common protein source in aquafeed for farmed fish. However, the demand for fishmeal is increasing but supply is stagnating or even decreasing and therefore is insufficient to meet demand. This has caused the increase of fishmeal price in global markets and thereby, incurs higher production costs. Thus, there is an urgent need to find a cheaper but suitable protein source to replace fishmeal in animal feed. The objective of this study is to evaluate the potential of Chrysomya megacephala (Fabricius, 1974) maggot meal as protein source in red tilapia (Oreochromis sp.) feed. Protein content of blowfly (C. megacephala) maggot meal extract was determined using three different colourimetric methods – Biuret method, dye-binding method and the method of Lowry et al. (1951). Protein estimation was performed after dissolution of maggot powder in 0.06 M sodium phosphate buffer, pH 7.0 both in the absence and presence of 1% (w/v) sodium dodecyl sulphate (SDS). Alternatively, the use of color reagent was made both before and after centrifugation of the dissolved mixture. Since dye-binding method could not be performed in the presence of SDS which its interferes with the process, both Biuret method and the method of Lowry et al. (1951) were employed using standard curves in presence of 1% (w/v) SDS. Two other methods, namely, Warburg-Christian method and semi-micro Kjeldhal method were also used to determine protein concentration. The inclusion of SDS and addition of color reagents before centrifugation of the dissolved sample showed a significant increase in the percentage of protein content compared to the results obtained under normal condition. A comparison of all these results supported the use of Biuret method and the method of Lowry et al. (1951) under specific iii conditions as the substitute for semi-micro Kjeldhal method for protein estimation. SDS-polyacrylamide gel electrophoresis of maggot meal extract showed the presence of both small and medium sized proteins ranging in molecular weight from 17 ― 83 kDa. Maggot meal powder derived from maggots hatched from eggs over a period of 4 days were also found to be rich in essential amino acids as proven by amino acid analysis. A feeding trial was performed for 60 days to evaluate the potential of this blowfly maggot meal to replace fish meal in red tilapia (Oreochromis sp.) feed. Five isonitrogenous and isoenergy fish meal diets formulated to contain 30% of protein and 20 kJ g-1 of gross energy were replaced by maggot meal at 0%, 25%, 50%, 75% and 100%. Fishes that were fed with 100% showed the highest survival rate (80%), percentage weight gain (239%), specific growth rate (2.02% per day) and protein efficiency ratio (0.3), and the lowest of food conversion ratio (1.34) as compared with other experimental diets. A selection experiment was conducted to improve the body weight of C. megacephala. After 10 generations of artificial selection, the body weight of C. megacephala maggot increased. Taken together, all these results suggested the suitability of maggot (C. megacephala) meal as a protein source in red tilapia feed.